(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This article examines the pragmatic functions of the infinitive in English literary text. It analyzes the ability of infinitive constructions to express authorial intention, emotivity, modality, evaluation, and persuasive impact. Based on examples from works of English literature (J. Austen, C. Dickens, V. Woolf, E. Hemingway), their role in organizing narration and forming the subjective-modal plane is revealed. The research results demonstrate that the infinitive in a literary text performs not only a grammatical but also a pragmatic function, realizing the author’s communicative strategies and contributing to the expression of cognitive-evaluative meaning.